Investigate The Availability Of Servant Leadership Characteristics Among The Administrative Leaders In Business Organizations In Dohuk Province And Diagnose Their Role In Achieving Organisational Excellence - Nori, Rang M.; Ahmed, Aveen M. S.; Dino, Chiya I. (Humanities Journal of University of Zakho, 2017)
The research aims to investigate the availability of Servant leadership characteristics among the administrative leaders in business organizations in Dohuk province and diagnose their role in achieving Organisational excellence. to address this issue theoretical framework has been presented on Servant leadership and Organisational excellence , hypotheses formulated to verify the relationship between the characteristics of Servant leadership and Organisational excellence , in order to verify the hypotheses ,number of fundamental questions within the questionnaire developed , which was the main tool for collecting field data and has answered by form (60) of individuals working in a number of business organizations in the province of Dohuk. Data was analyzed using averages, standard deviations, as well as simple linear regression analysis, Pearson correlation coefficient, and the results were extracted using statistical software (SPSS). The study found a number of conclusions the main was the significant correlation between the independent variable (Servant leadership) and Organisational excellence, and the existence of a significant effect of Servant leadership on Organisational Excellence. The study concluded with number of sugestions concerning the organizations under study was the most important need for the administrative leadership work in the surveyed organizations meet the needs of individuals working in the organization so that they can meet the challenges and rapid environmental changes to achieve Organisational excellence.